Weak electric field effect of MFC biocathode on denitrification. Issue 6 (December 2022) - Huang, Shan; Zhang, Jingran; Wang, Chuqiao; Zhu, Guangcan; Hassan, Mahdi
Abstract: Microbial fuel cells (MFCs) have been reported to enhance denitrification. However, it is difficult to investigate the denitrification enhancement mechanism under weak electric field (WEF) due to the multi-parameter variation in MFCs. In this study, a series of potentiostatic bioelectrochemical systems (BESs) for wastewater with a low COD/N ratio were constructed by simulating the MFC biocathode. The denitrification effect differences of the BESs under different constant potentials (−400, −200, +200 and +400 mV vs. Ag/AgCl) were investigated. The nitrogen removal pathway was identified by exploring the source and the flow direction of electrons in the biocathode. The electron transfer method in the biocathode and the influencing mechanism of the WEF on microorganisms was elucidated by electrochemical analysis, high throughput sequencing and PICRUSt2. The results showed that the WEF in MFCs could enhance the denitrification effect by increasing the biomass, the abundance of denitrifying functional bacteria ( Thauera, SM1A02, Plasticicumulans, Ignavibacterium, Methylopolylis ), the expression of functional genes (nasA, narGH, narI, narV, nirk, hcp, nosZ), and Nar and Nir enzyme activities, thereby providing electrons for the electroautotrophic denitrifying bacteria ( Thauera ). The electron transfer method between the biofilm of denitrifying bacteria and the solid cathode electrode mainly involved direct electron transfer, and there were at least two electroactive components, which might be related to Nar and Nir activities. These results have important theoretical significance and positive support for the application of microbial electrochemical systems and the realization of the advanced treatment of wastewater with a low COD/N ratio. Graphical Abstract: ga1